(3GdJNWjW h GdJfejI GdRQGYjIs - (3LhGO SYO(B, (3GdYGQas ((3YeGf(B:s (3OGQ GdQGjI(B,s, 2009)
(3GdJfejI h GdJNWjW GdGbJUGOj , CgejI GdRQGYI h NUGFUgG h GfhGYgG h fXegG , CSGSjGJ GdJNWjW GdRQGYj eY GdJfHD h GdJhbY aj gPG GdJNWjW , CSGdjH GdJNWjW h GfhGY GdNWW GdRQGYjI , ESJQGJjLjI GdJfejI GdRQGYjI h EbJUGOjGJgG , GdJfejI GdRQGYjI h GdGef GdZPGFj , OhQ eUGOQ GdejGg aj GdJfejI GdRQGYjIs
(3eQGLY U(B.163s
Keywords: (3GdJNWjWs; (3GdJNWjW GdEbJUGOjs; (3GdJNWjW GdRQGYjs; (3GdJfejI GdRQGYjIs